2022
DOI: 10.1177/13670069211058275
|View full text |Cite
|
Sign up to set email alerts
|

The non-native phonetic perception mechanism utilized by bilinguals with different L2 proficiency levels

Abstract: Aims: The present study investigated whether bilinguals differing in L2 proficiency are different in their non-native phonetic perception mechanism. Methodology: An event-related potential (ERP) experiment was conducted, in which high and low L2 proficiency bilinguals were asked to focus their attention on a muted film while listening pre-attentively to phoneme contrasts arranged in the Oddball paradigm. Non-native and native phonetic conditions were investigated in two separate blocks. Data and analysis: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 42 publications
(110 reference statements)
2
15
0
Order By: Relevance
“…Importantly, apart from the context of acquisition and the experimental setting per se , another factor which has been demonstrated to affect the pre-attentional phoneme discrimination in L2 is the level of proficiency. Liang and Chen (2022) found different neural responses in adult Mandarin learners of English with high and low proficiency levels. When processing non-native phonemic contrasts, bilinguals with high L2 proficiency showed the MMN response followed by late discriminative negativity (LDN).…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Importantly, apart from the context of acquisition and the experimental setting per se , another factor which has been demonstrated to affect the pre-attentional phoneme discrimination in L2 is the level of proficiency. Liang and Chen (2022) found different neural responses in adult Mandarin learners of English with high and low proficiency levels. When processing non-native phonemic contrasts, bilinguals with high L2 proficiency showed the MMN response followed by late discriminative negativity (LDN).…”
Section: Introductionmentioning
confidence: 89%
“…This intention is very strongly intertwined with their perception of foreign phonemes relative to native phonemes. Previous research has found significant neural differences in native as opposed to non-native phonemic perception, suggesting reduced phonemic discrimination mechanisms in the second language (L2) when compared with the first language (L1) (e.g., Jakoby et al, 2011 ; Song and Iverson, 2018 ; Liang and Chen, 2022 ). However, the listener’s auditory discrimination abilities in L3/L n remain largely understudied.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations